Faktor-Faktor yang Berhubungan dengan Pemberian ASI Eksklusif di Klinik Pratama Daniel - Tiarmin Sitorus; Parida Hanum; Rostanita Silaban; Resmi Marpaung; Asnaria Naibaho (Malahayati Nursing Journal, 2025)
ABSTRACT Problems in the practice of exclusive breastfeeding are delayed initiation, not implementing exclusive breastfeeding and early discontinuation of breast milk consumption less than 6 months so that this causes the growth and development of infants is not optimal. The purpose of this study was to determine the factors associated with exclusive breastfeeding. The type of research used was quantitative using an analytic observational design research design with a cross sectional approach. The population in this study were all mothers who had babies 0-6 months totaling 105 people. The subject retrieval technique used purposive sampling of 83 people. The data collection method used was to use a questionnaire that was prepared to measure variables. The variables measured were age, education, occupation, knowledge, values/cultural customs, family support and health worker support. The research data analysis was univariate and bivariate analysis with chi square test. The results explained that there was a relationship between age (p=0.012), education (P=0.006), occupation (P=0.008), knowledge (P=0.015), cultural values/customs (P=0.009), family support (P=0.006) and health worker support (P=0.022) with exclusive breastfeeding. The conclusion of this study is that there is a relationship between age, education, occupation, knowledge, cultural values/customs, family support and health worker support with exclusive breastfeeding.  Keywords: Age, Education, Occupation, Knowledge, Cultural Norms/Customs, Family Support, Health Worker Support, Exclusive Breastfeeding  ABSTRAK Masalah-masalah dalam praktik pemberian dalam pemberian ASI eksklusif adalah delayed initiation, tidak menerapkan ASI eksklusif dan penghentian dini konsumsi ASI kurang dari 6 bulan sehingga hal ini menyebabkan tumbuh kembang bayi tidak optimal. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan pemberian ASI eksklusif. Jenis penelitian yang digunakan adalah kuantitatif dengan menggunakan desain penelitian desain observasional analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua ibu yang memiliki bayi 0-6 bulan berjumlah 105 orang. Teknik pengambilan subjek menggunakan purposive sampling sebanyak 83 orang. Metode pengumpulan data yang digunakan adalah dengan menggunakan kuesioner yang disusun untuk mengukur variabel. Variabel yang diukur adalah usia, pendidikan, pekerjaan, pengetahuan, nilai-nilai/adat budaya, dukungan keluarga dan dukungan petugas kesehatan. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan bahwa terdapat hubungan usia (p=0,012), Pendidikan (P=0,006), pekerjaan (P=0,008), pengetahuan (P=0,015), nilai/adat budaya (P=0,009), dukungan keluarga (P=0,006) dan dukungan petugas kesehatan (P=0,022) dengan pemberian ASI eksklusif. Kesimpulan penelitian ini adalah Terdapat hubungan usia, pendidikan, pekerjaan, pengetahuan, nilai/adat budaya, dukungan keluarga dan dukungan petugas kesehatan dengan pemberian ASI eksklusif.  Kata Kunci: Usia, Pendidikan, Pekerjaan, Pengetahuan, Norma/Adat Budaya, Dukungan Keluarga, Dukungan Petugas Kesehatan,  ASI Eksklusif.